2008
DOI: 10.1056/nejmoa0707615
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Therapy of Advanced Chronic Hepatitis C with Low-Dose Peginterferon

Abstract: Background-In patients with chronic hepatitis C who do not have a response to antiviral treatment, the disease may progress to cirrhosis, liver failure, hepatocellular carcinoma, and death. Whether long-term antiviral therapy can prevent progressive liver disease in such patients remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
399
2
12

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 429 publications
(423 citation statements)
references
References 19 publications
10
399
2
12
Order By: Relevance
“…30 Recently Di Bisceglie et al reported that low-dose maintenance therapy with peginterferon failed to reduce the incidence of HCC in HCV-positive patients with bridging fibrosis. 31 However, the annual incidence rate of HCC was approximately 1% in their study, in which the patients were around 50 years old. A Japanese retrospective study found that interferon therapy reduced the annual incidence of HCC from 6%-8% to 4%-5% in cirrhotic patients aged about 60 years.…”
Section: Discussionmentioning
confidence: 84%
“…30 Recently Di Bisceglie et al reported that low-dose maintenance therapy with peginterferon failed to reduce the incidence of HCC in HCV-positive patients with bridging fibrosis. 31 However, the annual incidence rate of HCC was approximately 1% in their study, in which the patients were around 50 years old. A Japanese retrospective study found that interferon therapy reduced the annual incidence of HCC from 6%-8% to 4%-5% in cirrhotic patients aged about 60 years.…”
Section: Discussionmentioning
confidence: 84%
“…It is also important to note that there were no improvements in fibrosis stage or progression after long-term maintenance therapy with pegylated interferons or in posttransplant patients who failed to achieve SVR with HCV therapy. 13,14 The objective of this analysis was to assess the histologic response to interferon-based therapies, based on changes in the METAVIR necroinflammatory (NIF) activity and fibrosis scores in a large group of patients with varying degrees of virologic response, time to HCV RNA undetectability, and duration of viral suppression.…”
mentioning
confidence: 99%
“…In contrast, Giannini et al [58] reported that nonresponse to a previous antiviral therapy is an important determinant of reduced response to full-dose therapy with peginterferon and ribavirin in cirrhosis and portal hypertension. Di Bisceglie et al [59] noted that long-term half-dose peginterferon therapy did not suppress disease progression and HCC development in cirrhotic patients who did not respond to initial peginterferon plus ribavirin therapy and concluded that this therapy is not indicated for these patients.…”
Section: Antiviral Therapy For Hepatitis B Virus Related Cirrhosismentioning
confidence: 99%